Pengaruh Kemudahan dan Tingkat Kepercayaan pada Platform Investasi Online serta Literasi Keuangan terhadap Minat Berinvestasi di Pasar Modal Syariah: Studi Kasus pada Masyarakat Muslim Kota Padang - Pratama, Novio Dyfa; Yuliafitri, Indri (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The development of information technology in the financial sector makes all financial activities easier and more practical, including investment activities in the Islamic capital market with the emergence of various fintech-based online investment platforms. However, with the various conveniences offered on online investment platforms, there is still a large comparison between the number of investors and the number of people of productive age in Indonesia, which shows that there are still many Indonesian people who do not have an interest in investing in the capital market. Therefore, the author examines the factors that influence people's interest in investing in the Islamic capital market. This research aims to analyze the influence of the variable perceived ease of online investment platforms, level of trust in online investment platforms, and financial literacy on the investment interest of the Padang City Muslim community in the sharia capital market. This research was carried out using a questionnaire with a purposive sampling technique because there are special criteria to become respondents in this research. The sample was 121 respondents from the Muslim community of Padang City. The data obtained was managed and analyzed using multiple linear regression analysis with the help of SPSS software. This research shows that the variables of perceived ease of online investment platforms, level of trust in online investment platforms, and financial literacy have a positive and significant influence on the investment interest of the Padang City Muslim community in the sharia capital market.